Temperature driven failure of carbon epoxy composites – A quantitative full-field study. (8th February 2018) - Wilson, P.R.; Cinar, A.F.; Mostafavi, M.; Meredith, J.
Abstract: Aerospace composites are exposed to low temperatures that induce high levels of stress within the material. This is sufficient to induce fractures and eventually delaminations and failure. Thus, understanding how these temperature induced translaminar fractures can be reduced is an important area of research. This work investigates cross-ply unidirectional (UD) and woven (W) carbon fibre laminates with MTM46 epoxy to assess how the cure schedule (low temperature, LTC and high temperature, HTC) effect temperature driven fractures. A novel digital image correlation technique was applied to determine in-situ fracture progression versus temperature. Thermal techniques investigated the degree of cure, resin plasticity, thermal expansion and beta transition effects. The cure schedule for carbon epoxy laminates has a marked effect on quantity of manufacturing induced fractures and the temperature at which temperature induced internal fracture occurs. This work has demonstrated that a lower temperature cure is more robust against temperature driven fracture despite having a larger coefficient of thermal expansion (CTE) and similar levels of plasticity. Low temperatures induce high internal stresses but the residual stress resulting from high temperature cure is of greater concern. DIC is an excellent method to determine onset and progression of translaminar fracture as well as the behaviour of composite materials subject to temperature effects. This work is of great benefit when considering the design of CFRP structures subject to low temperature loading, furthermore the data can be used to more accurately model this phenomena in future.